Комунікативна діяльність та ділове спілкування у роботі публічної служби. - Плотніченко, Світлана Романівна; Plotnichenko, Svitlana; Вороніна, Юлія Євгенівна; Voronina, Yuliia (Мелітополь, ТДАТУ, 2021)
UKR: Основа успіху ділової людини, яке б заняття вона не обрала, складається у створенні клімату співробітництва, довіри, уваги. Тому спілкування з людьми – це наука й мистецтво. Тут важливі не тільки природні здібності людини та її бажання спілкуватись, але й знання законів спілкування. Керівники повинні зрозуміти, що для успішної діяльності вони можуть і повинні навчитись орієнтуватись у психологічних підхо дах до партнерів, адекватно розуміти реальність, обирати такі способи ділового спілкування, які будуть сприяти успіху як у професійній діяльності, так і у житті. Управлінці повинні звернути особливу увагу на те, що проблема спілкування є одною з найважливіших у житті ділової людини. Взаємодіючи з іншими людьми, сучасній людині необхідно знати основні правила етич ної поведінки та спілкування для того, щоб ці контакти не призводили до конфліктів, не порушували соціальну рівновагу, а повсякденне ділове спілкування було гармонійним і корисним.\\\\\\\\\\\\\ ENG: The manager is a special concentration of abilities and the ability to communicate and create conditions for the disclosure of personal potential of employees, now it is the essential bases of communication in the public ser vice that are subject to revision. This is explained by the fact that the attitude of the actors of managerial communica tion to each other as objects of sometimes can very often lead to the demoralization of relations, depleted functioning, a formal approach to the profession. The basis of success of a business person, no matter what occupation he chooses, is to create a climate of cooperation, trust and attention. Therefore, communication with people is a science and an art. Here are important not only the natural abilities of man and his desire to communicate, but also knowledge of the laws of communication. Managers must understand that for successful activities they can and should learn to navigate in psychological approaches to partners, to adequately understand the reality, to choose such ways of business communi cation that will contribute to success both in professional activities and in life. Managers should pay special attention to the fact that the problem of communication is one of the most important in the life of a business person. When interacting with other people, modern man needs to know the basic rules of ethi cal behavior and communication so that these contacts do not lead to conflicts, do not disturb the social balance, and everyday business communication was harmonious and useful. Business communication ensures the effective realization of management goals, unites people into a single society, a single country, a single community with a single government, that is, it cements society. The purpose of the develop ment of business communication is the formation of effective management relations in the work of public service.
Communicative activity and business communication in the work of the public service.
Keywords: Комунікація; комунікативна діяльність; зворотний потік інформації; самореалізація службовців; види ділового спіл кування; некваліфікована комунікація; Communication; communicative activit; reverse flow of information; unqualified communication; self-realization of employees; types of business commu nication